Women’s mental health during late pregnancy: A survey conducted in Shandong Province, China - Li, Yijie; Yu, Huihui; Shen, Kaifang; Long, Jing (Fortschritte der Neurologie · Psychiatrie, 2024)
Background  The study aimed to investigate the general mental health status and its associated factors in women during late pregnancy. The objective was to provide a scientific basis for developing psychological interventions tailored to this specific population.Methods  The research was conducted from May 2021 to July 2022, involving the recruitment of 200 women attending maternal and child health clinics for their late-pregnancy checkups. Data collection was carried out using a comprehensive approach, involving several validated tools. The participants completed a general demographic and sociological questionnaire along with four standardized psychological assessment scales: the 12-item General Health Questionnaire (GHQ-12), the Athens Insomnia Scale (AIS-8), the Generalized Anxiety Disorder 7 (GAD-7), and the 9-question Patient Health Questionnaire (PHQ-9). A total of 200 valid questionnaires were collected for analysis. Results  The study revealed that the overall prevalence of positive detection of general mental health problems in women during late pregnancy was 11%. Significant differences were observed in the positive detection rate of general mental health status based on various factors such as the quality of relationships with husbands, pregnancy intentions, insomnia, anxiety, and depression (p<0.01). Furthermore, participants with general mental health problems displayed notably higher scores on the AIS-8, PHQ-9, and GAD-7 scales compared to those without such problems (p<0.01). Regression analysis indicated that pregnancy intention and PHQ-9 scores were influential factors affecting the general mental health of women during late pregnancy (p<0.05).Conclusion  The study highlights high rates of general mental health problems during late pregnancy, with unplanned pregnancy and elevated depression scores as key risk factors. Regular mental health screening and targeted interventions are essential to support women during this critical period and enhance the well-being of both mothers and babies.
Keywords: pregnancy; women; mental health; depression; anxiety; Generalized anxiety disorder